Transforming dental education: interactive and student-centered learning with team-based learning in the undergraduate program - Teun J. de Vries; Katie L. Crouwel; Erica Vogelzang; A. Isa Levert; Egbert Neels; Amber de Wilde; Pepijn Koopman; Denise E. van Diermen; Geerling E. J. Langenbach; E. Etienne Verheijck (Frontiers in Medicine)
World-wide, educational curricula have made a transition toward (inter)active student-centered learning and teaching. To incorporate consistency within a curricular reform, it is important to make choices that are applied to all courses. Here we describe the implementation of team-based learning (TBL), an effective educational approach for activated learning at a dental school. TBL stimulates students to participate actively in their own learning process. This team-oriented method fosters problem solving, critical academic reasoning, clinical decision-making and communication skills among students, already early in their educational career. In the first year of the undergraduate program, TBL was introduced as a mandatory component, constituting 10% of the teaching activities and overall grade. To facilitate this transition, a dedicated team of teachers and educationalists (the TBL team) was formed to prepare the transition. The initial step involved establishing a TBL course and conducting training sessions for faculty to familiarize them with this new teaching methodology. Teachers received constructive feed-back on their own TBL application session. Due to the Covid-19 pandemic, TBL was introduced as an online variant, requiring close collaboration with IT-services. Halfway through the academic year, the implementation was evaluated through separate panel discussions with students and teachers separately. Overall, TBL was perceived favorably by both staff and students. Students appreciated the team work and noted that TBL added value to their learning process. This was also the outcome of the end of the academic years’ student survey on TBL, where especially questions on collaborative teamwork scored 4.22 on average on a 1–5 Likert’s Scale. TBL was inspiring for teachers, the student teams of TBL provided a safe environment for students to voice their thoughts. The activating nature of TBL was recognized as beneficial, though it requires continuous effort and motivation from instructors. Coaching and guiding were perceived as highly effective instructional methods. Some teachers acknowledged the challenge of transitioning from a traditional “one-person” show approach to a more collaborative teaching style. Both evaluations facilitated further refinement of the TBL approach. Particularly, during the social intercourse-deprived Covid-19 era, the fixed-groups format of TBL helped students to experience a sense of belonging.